The production of hydrogen-rich gas from sludge steam gasification catalyzed by Ni-based sludge char prepared with mechanical ball-milling. (December 2021) - Chen, Aixia; Hu, Ruirui; Han, Rong; Wei, Xiao; Tian, Zheng; Chen, Li
Abstract: In this study, a Ni-based sludge coke catalyst was prepared by mechanical ball-milling and mild injection to produce high-quality hydrogen-rich gas through the gasification of sludge. The effects of different factors, such as ball milling time, gasification temperature, NiO loading rate and steam flow rate on the gasification characteristics of the Ni-based sludge coke were investigated. The results showed that the optimum process conditions were the ball-milling time of 10 min, gasification temperature of 900 °C, NiO loading rate of 20% and steam flow rate of 1 g min −1 . Under these conditions, the gas production efficiency was improved, with gas and H2 production rates of 0.76 m 3  kg −1 and 0.34 m 3  kg −1, respectively. Temperature is a key factor of gasification. The gas yield and H2 yield at 900 °C were 38 times and 85 times higher than those at 500 °C, respectively. The FTIR and XRD analysis further revealed that the selection of an appropriate ball-milling time caused the NiO to be evenly distributed on the biochar, thereby improving its catalytic performance. While, increasing the temperature promoted the full pyrolysis of organic matter and the secondary decomposition of tar, which improved the gasification efficiency. The results obtained here allow optimization of the technical parameters for the generation of hydrogen-rich gas by sludge gasification, thereby providing a theoretical basis for the production of high-quality gas through the catalytic gasification of Ni-based biochar. Highlights: The sludge resource utilization is realized, and hydrogen-rich gas is produced by sludge gasification. NiO is successfully loaded on sludge coke by mechanical ball milling to increase the volume fraction of combustible gas. The introduction of water vapor improves the quality of syngas.